Golden ratio beauty as scientific function (Lebenswelt. Aesthetics and philosophy of experience., 2018)
Normally when one is considering the golden ratio in the history of ideas, one is often looking at it as an aesthetic principle – usually associated with Greek art, sculpture and mathematics. However, in recent years the prevalence of the golden ratio within a broad range of scientific disciplines has brought its role in the perfection of science to the forefront. I would like to collapse these two areas by proposing a somewhat novel way of looking at the aesthetics of the golden ratio: its pervasive expression in scientific form and function is the basis of the aesthetics in the world. Therefore, science contains the same mathematical beauty as found in artistic expression. The golden ratio guides the Chaos Border of Kolmogorov, Arnold, and Moser (KAM theorem) and it can be found hidden in all elementary particles, and even in the proportions of dark matter and energy relative to visible matter and energy. It is evident in the structure and growth functions of plants and animals and it can be found in the physiological functions of humans. It now appears that without the golden ratio, we would not have the form or function of the proton, cell, athlete, horse, species, planet, solar system or galaxy.